USE OF INNOVATIVE LECTURES AND QUALITY CONTROL OF KNOWLEDGE AND SKILLS AT POSTGRADUATE STUDY STAGE - Potyazhenko, М.М.; Sokolyuk, N.L.; Nastroha, T.V.; Kitura, O.E.; Lulca, N.А. (World of Medicine and Biology, 2016)
The paper presents the types of lectures and control of knowledge and skills, used the most widely at the stage of post-graduate education of internship doctors. It has been proved that the use of innovative lectures and knowledge quality control helps to improve the professional level of medical interns, increase the competitive ability of graduates.
Keywords: quality training; lecture; control; postgraduate education